EFFECT OF IMMUNE CELLS ON THE BEHAVIORAL ACTIVITY LEVEL OF MICE (СВАхC57BI/6)F1 DURING ONTOGENESIS - O. S. Anikeeva; T. Ya. Abramova; V. A. Kozlov (Бюллетень сибирской медицины)
The features of forming of the orientation and exploratory behavior level (OEB) was established on sexually immature animals – mice (CBAxC57/Bl)F1, which underwent triple transplantation of splenocytes from adult syngeneic animals with a certain level of OEB during ontogenesis. Obtained data testifies an increase the part of passive animals in recipients group receiving splenocytes from low-level in behavior donors and an increase the part of animals with average level of OEB in recipients group receiving cells from donors with high OEB level and immature control group. The associations of recipients behavioral activity level with structural and functional features of donor cells was revealed: a relative increase in the OEB level under splenocytes transfer from donors with activated monocyte-macrophage link of immune system and a supression of OEB – from donors with activated T-cells.